Understanding the use of game advertising for luxury brands: The impact of brand coolness on brand equity - Romero, Maria Inês Relvas (2022)
In a world where digital continues to develop, there is an increasing need for brands to stand out from the competition. To achieve that it is necessary that they make investments in order to be seen as credible brands, but also in order to represent an added intangible value for the consumer. The aim of this study is then to understand if the use of Game Advertising in Luxury Brands will have that impact. Taking as a starting point the Brand Credibility associated to Luxury Brands, this study tries to understand its relationship with their Brand Coolness and, consecutively, the impact on their Brand Equity. It also seeks to explain if there are characteristics intrinsic to each individual that can moderate this relationship. To carry out this analysis, the case of the Louis Vuitton brand with the League of Legends Game was used as an example and a questionnaire was shared, reaching 417 individuals. The data processing and interpretation processes were performed using IBM SPSS Statistics 28 and SmartPLS4 software. It was possible to conclude that Brand Credibility increases consumers' perception of Brand Coolness, just as it also positively impacts Perceived Quality, Brand Awareness and Loyalty of a consumer towards a brand and, consequently, its Brand Equity. The fact that individuals are consumers of Luxury Brands and that they are already aware of other brands using Game Advertising also has a positive impact on Brand Awareness.